1985
DOI: 10.1159/000226067
|View full text |Cite
|
Sign up to set email alerts
|

Alloantigen-Activated Lysis of Syngenic Tumor Augmented by Allogenic Lymphocytes as Cold Targets

Abstract: In the past, most work in tumor immunology involved attempts to demonstrate tumor-specific transplantation antigens; however, recent in vitro work has shown that it is not necessary to sensitize to a specific tumor antigen to achieve lysis of syngenic tumor cells. Responder spleen cells from B6AF1 mice (H-2ab) were sensitized in mixed lymphocyte cultures (MLC) to alloantigens on spleen cells from B10.D2 (H-2d) mice. In cell-mediated lympholysis (CML) assa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1985
1985
1987
1987

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…[4] showed that activation of T cells to single or multiple alloantigens resulted in a cytolytic cell that would lyse neoplastic tissues in preference to normal. The ha plotype of tumor cells lysed was not limited to the haplotype(s) of stimulator cells used for sensitization [5]. Grimm el al.…”
Section: Introductionmentioning
confidence: 99%
“…[4] showed that activation of T cells to single or multiple alloantigens resulted in a cytolytic cell that would lyse neoplastic tissues in preference to normal. The ha plotype of tumor cells lysed was not limited to the haplotype(s) of stimulator cells used for sensitization [5]. Grimm el al.…”
Section: Introductionmentioning
confidence: 99%